Stress concentration of perforated cement sheath and the effect of cement sheath elastic parameters on its integrity failure during shale gas fracturing - Bu, Yuhuan; Yang, Heng; Zhao, Lingyun; Guo, Shenglai; Liu, Huajie; Ma, Xiaolong (Frontiers in Materials, 2022)
Due to the extremely low porosity and permeability of shale, fracturing is often used to develop shale gas reservoirs. During shale fracturing, extremely high fracturing pressure may invalidate the integrity of the cement sheath and bring hidden dangers to the safe development of shale gas. This paper compares the stress state of the three-dimensional unperforated and perforated finite element model of casing-cement sheath-formation to obtain the influence of perforation on the stress concentration and failure area of the cement sheath. The stress state comparison of three sets of perforation models with different hole densities and diameter verifies the stress concentration law of perforation on the cement sheath. By studying the effects of the elastic modulus and Poisson’s ratio of the cement sheath on the maximum tensile and compressive stresses of the cement sheath under fracturing pressure, the integrity failure form of the cement sheath and the measures for integrity failure are obtained. The results show that the peak stress concentration of the perforated cement sheath is about twice the normal value of the stress. The damaged area is the two ends of the perforation, the shape is similar to the bottom surface of the elliptical cone, and the thickness is up to half of the wall thickness of the cement sheath. The line length of the largest damage area is 4.5 times the diameter of the hole. Under fracturing conditions, the cement sheath generally undergoes tensile failure. The lower the elastic modulus and Poisson’s ratio of the cement sheath, the smaller the tensile stress of the cement sheath, and the less likely it is to cause tensile failure.